Elite Marathoners Run Faster With Increasing Temperatures in Berlin Marathon - Knechtle, Beat; Valero, David; Villiger, Elias; Alvero Cruz, José Ramón; Scheer, Volker; Rosemann, Thomas; Nikolaidis, Pantelis T. (Frontiers in Physiology, 2021)
The influence of environmental conditions has been investigated for different marathon races, but not for the Berlin Marathon, the fastest marathon race course in the world. The aim of this study was to investigate the potential influence of environmental conditions such as temperature, precipitation, sunshine, and atmospheric pressure on marathon race times in the Berlin Marathon since its first event in 1974 to 2019. A total of n=882,540 valid finisher records were available for analysis, of which 724,135 correspond to male and 158,405 to female runners. We performed analyses regarding performance levels considering all finishers, the top three, the top ten, and the top 100 women and men. Within the 46 years of Berlin marathons under study, there was some level of precipitation for 18 years, and 28 years without any rain. Sunshine was predominant in 25 of the events, whilst in the other 21, cloud cover was predominant. There was no significant trend with time in any of the weather variables (e.g., no increase in temperature across the years). Overall runners became slower with increasing temperature and sunshine duration, however elite runners (i.e., top three and top ten) seemed to run faster and improved their race times when the temperature increased (with women improving more than men). Top ten women seemed to benefit more from increasing temperatures than top ten males, and male top 100 runners seemed to benefit more from increasing temperatures than female top 100 runners. In the top three sub-group, no differences were observed between male and female correlations. In summary, in marathoners competing in the Berlin Marathon between 1974 and 2019, increasing temperatures and sunshine duration showed a different effect on different performance levels where overall runners (i.e., the general mass of runners) became slower with increasing temperature and sunshine duration, but elite runners (i.e., top three, top ten) became faster with increasing temperatures where sex differences exist.